ALIH TEKNOLOGI MELALUI PERJANJIAN LISENSI KAITANNYA DENGAN UNDANG-UNDANG NOMOR 14 TAHUN 2001 TENTANG PATEN - Romli Mubarok (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2007)
The present world is dominated by sciences and technologies. Countries possessing the two variables might be able to dominate the world, since sciences and technologies constitute critical infrastructures determining the shapes of global supra-structures The development of technologies in Indonesia has indeed not been able to play as important roles as played by some other advanced countries. Therefore, the government of Indonesia keeps encouraging the development of technologies particularly through technological transfers done via advantageous licensing contracts. In addition, the government of Indonesia also try to keep encouraging Indonesian citizens to make investments, both individually and in groups, regulated by the Indonesian Law for Patents, Number 14, 2001